Lifetime risk of rheumatoid arthritis-associated interstitial lung disease in MUC5B mutation carriers. Issue 12 (3rd August 2021) - Palomäki, Antti; ,; Palotie, Aarno; Koskela, Jukka; Eklund, Kari K; Pirinen, Matti; ,; Ripatti, Samuli; Laitinen, Tarja; Mars, Nina
Abstract : Objectives: To estimate lifetime risk of developing rheumatoid arthritis-associated interstitial lung disease (RA-ILD) with respect to the strongest known risk factor for pulmonary fibrosis, a MUC5B promoter variant. Methods: FinnGen is a collection of epidemiological cohorts and hospital biobank samples, integrating genetic data with up to 50 years of follow-up within nationwide registries in Finland. Patients with RA and ILD were identified from the Finnish national hospital discharge, medication reimbursement and cause-of-death registries. We estimated lifetime risks of ILD by age 80 with respect to the common variant rs35705950, a MUC5B promoter variant. Results: Out of 293 972 individuals, 1965 (0.7%) developed ILD by age 80. Among all individuals in the dataset, MUC5B increased the risk of ILD with a HR of 2.44 (95% CI: 2.22 to 2.68). Out of 6869 patients diagnosed with RA, 247 (3.6%) developed ILD. In patients with RA, MUC5B was a strong risk factor of ILD with a HR similar to the full dataset (HR: 2.27, 95% CI: 1.75 to 2.95). In patients with RA, lifetime risks of ILD were 16.8% (95% CI: 13.1% to 20.2%) for MUC5B carriers and 6.1% (95% CI: 5.0% to 7.2%) for MUC5B non-carriers. The difference between risks started to emerge at age 65, with a higher risk among men. Conclusion: Our findings provide estimates of lifetime risk of RA-ILD based on MUC5B mutation carrier status, demonstrating the potential of genomics for risk stratification of RA-ILD.